An assessment of the role of non-state actors in development of community-based ecotourism in Kenya’s Western tourist circuit - Nyamweno, Isaac M.; Okotto, Lorna G.; Tonui, Warkach K. (International Journal of Liberal Arts and Social Science, 2016)
This study was mounted to provide better understanding of the role non-state actors (NSAs) are currently playing in the context of community-based ecotourism in the western tourist circuit of Kenya. The motivation to carry out this research stemmed from the fact that there is dearth of information on this important area of scientific inquiry. While the existence of NSAs engaged in various aspects of ecotourism development in the western circuit is not contested, this constituency of stakeholders has not been sufficiently studied and their role systematically documented. The cross sectional study carried out in 2015 involved 114 NSAs drawn from 9 of the 12 counties that form the circuit. The study mainly benefited from primary data obtained with the aid of questionnaires and in-depth discussions with key informants and processed with the help of the Statistical Package for Social Sciences (SPSS). The study established that NSAs that are registered as nongovernmental organizations (NGOs), Community-Based Organizations, Community Forest Associations (CFAs), Cooperatives, Business Management Organizations (BMOs) are engaged in diverse roles including but not limited to product development and diversification, advocacy, tour guiding and nature interpretation, research, construction of support infrastructure facilities, provision of a range of accommodation facilities including home stays and guest houses and enhancing accessibility to sites. The study further established that NSAs receive different types of support from other organizations including government ministries/departments, public universities, umbrella organizations and the international community. This paper argues that NSAs play a critical role in ecotourism development but require increased and sustained support from other development partners in public and private sector
Keywords: Ecotourism; Non-state Actors; Western Tourism Circuit of Kenya